The usage of orally gavage and topically applied omega -3 in the treatment of experimental gingivitis in rats. (Mustansiria Dental Journal, 2022)
AbstractAim of the study:   This study aimed to evaluate  effects of omega 3 polyunsaturated fatty acids  on ligation induced gingivitis in rats through the immunological analysis for rat’s gingival tissue level of tumor necrotic factor-α( TNF-α) .Materials and methods: The gingivitis was induced for rats by ligation around lower central incisors. Fifty animals with the induced gingivitis were divided into: five animals were sacrificed at the first day after removal of ligature, and fifteen animals as positive control group. Fifteen animals were used as 1st treatment group with orally gavage omega 3 polyunsaturated fatty acid and fifteen animals as 2nd treatment groups with topically applied omega3 a Five animals were used as negative control groups  (-ve) group.  Animals  were sacrificed and  tissue sections were evaluated for  Tumor necrotic factor –α (TNF-α) levels, this biomarker  were measured by ELISA method for  four times, first  after ligation removal (day zero), three days, one week and two weeks for immunological analysis.Results: The result showed that level of TNF-α were significantly lower in  systemic treatment groups in comparison with positive control groups in all duration of study, and there were significant difference between topical treatment groups on the 3rd and 7th  days and no significant differences on the 14th day  after removal of ligature in comparison with (+ve) ,also there was  no significantdifference between these two treatment groups in all duration of study. T-test  used for  statistical analyses, with p 0.001 as high significant.Conclusion:  orally gavage and topical application of omega-3 FAs is effective  treatment for reduction of  inflammation in  gingivitis, resulting in lower level of TNF-α.